Developing English Environmental Awareness Mini Posters at Dinda Resort Beach - Afore Tahir Harefa; Agnes Zendrato; Arni Mendrofa; Alfina Mendrofa (Al Hikmah: Journal of Education, 2026)
This research aims to develop English environmental awareness mini posters implemented directly at Dinda Resort Beach as an educational intervention and learning product. The study was conducted based on real field conditions where environmental issues, particularly improper waste disposal, were frequently observed. This research employed a Research and Development (R&D) method adapted from Borg and Gall, integrated with a qualitative descriptive approach. The researcher was directly involved in all stages, including needs analysis, product design, development, implementation, and evaluation. Data were collected through field observations, interviews with visitors and local staff, and documentation. The findings indicate that the developed mini posters were appropriate, The indicators that the mini poster is understandable and effective in promoting environmental awareness are: the message is clear and easy to understand, the language used is simple and appropriate, the poster includes a clear call to action, the content is relevant to environmental issues, the visuals support the message effectively. This study contributes to English environmental education through field-based learning and community engagement